Effect of dietary protein level on growth performance of tinfoil barb (Barbonymus schwanenfeldii) - Noor Fadliana Johari. (Universiti Putra Malaysia, 2015)
Tinfoil barb (Barbonymus schwanenfeldii) is a commercially valuable fish but information on its dietary requirement for aquaculture production in lacking. This study was aimed to measure the effect of dietary protein level on the growth performance of tinfoil barb juveniles. A total of 240 of tinfoil barb juveniles with an average weight of 2.36 g were random;y and equally allocated to each of twelve aquariums with a volume of 25 L. Fish were fed with isoenergetic aquafeed containing different protein levels (35, 40, 45 and 50 g'kg-1) based on 4% of the body weight twice a day at 0800 and 1700 hours fir 84 days. Growth performance, feed efficiency and body composition of the fish were evaluated. The feed treatment did not show significant differences for all of the growth parameters tested (P>0.05). It can be concluded that the growth performance on tinfoil barb juveniles were not affected by the dietary protein level from as low as 35 to 50 g'kg-1.